Early warning indicators for the German banking system: A macroprudential analysis - Nadya Jahn; Thomas Kick (Deutsche Bundesbank, 2012)
Over the past two decades, Germany experienced several periods of banking system instability rather than full-blown banking system crises. In this paper we introduce a continuous and forward-looking stability indicator for the banking system based on information on all financial institutions in Germany between 1995 and 2010. Explaining this measure by means of panel regression techniques, we identify significant macroprudential early warning indicators (such as asset price indicators, leading indicators for the business cycle and monetary indicators) and spillover effects. Whereas international spillovers play a significant role across all banking sectors, regional spillovers and the credit-to-GDP ratio are more important for cooperative banks and less relevant for commercial banks.
Keywords: C23; E44; G01; G21; 330; Early Warning Indicators; Banking System Stability; Regional Spillover Effects; Panel Regression Techniques